PSYCHOLOGICAL DEPICTION IN THE PHILOSOPHICAL NOVEL ‘THE ROAD” (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
Ulugbek Hamdam’s novel “The Road” belongs to the category of non-traditional narratives. In a number of works created after the independence of Uzbekistan, the use of the stream of consciousness technique, the interweaving of dream and reality, and the depiction of inner experiences have been directed toward portraying the fate of a person in search of self-identity. “The Road” is one of the prose works that introduced a new direction in Uzbek literature, where the artistic synthesis of Eastern and Western traditions is vividly manifested. As a philosophical novel, “The Road” foregrounds, already in its title, the central leitmotif of the author’s style—the interpretation of the relationship between the universe and humankind based on new principles. In Hamdam’s prose, the images of the traveler and the wayfarer, along with postmodern elements such as symbolism and intertextuality, are clearly represented. Although the main idea of postmodern literature is the perception of the world as “chaos,” in contrast to this notion, the novel reflects the author’s Eastern philosophical perspective as a solution to the meaning of human existence and the relationship between the universe and man. While the form of expression carries Western features, its essence is imbued with Eastern thought. Thus, humanity’s eternal problems find artistic resolution in the synthesis of Eastern and Western intellectual traditions.